Regenerative Medicine applied in the treatment of bone defects craniofacial complex - Denia Morales Navarro (Editorial Ciencias Médicas, 2015)
Introduction: regenerative medicine is a charming area of research in the biomedical sciences, it constitute a promising therapeutic alternative for expansion in the treatment of skeletal bone defects, including the craniofacial complex. Objective: to review the literature on the use of regenerative medicine in the treatment of craniofacial bone defects. Methods: a review was conducted in the period from June to July 2013. Impact journals from Web of Sciencies related to this topic were evaluated (28 journals) and 2 Cuban magazines. Were consulted databases referativos systems such as MEDLINE, PubMed and SciELO with the use of descriptors such as "craniofacial bone defects", "craniofacial regenerative medicine", "bone regeneration", "bone reconstruction", "bone scaffolds" and its Spanish counterparts. We included articles in English and Spanish and publications of the last five year, except for one. 115 articles were obtained, confined the study to 51 that focused this issue more comprehensively. A book was reviewed. Results: by analyzing the behavior of the articles on the subject of study with respect to their representation in the various scientific journals where they were published, 11.8% of them corresponded, respectively, to the Journal of Oral and Maxillofacial Surgery and The Journal of Craniofacial Surgery. The remaining items were evenly distributed among the other magazines. Conclusions: all these publications agree pronounce that we have entered a new era in orofacial bone regeneration, where improved osteoinductive materials, CM based therapies, among other elements of this branch of research, can be used to improve and accelerate desirable clinical outcomes in areas such as trauma, distraction, craniofacial defects, critical size and excision of pathological atrophy alveolar osteonecrosis and elevated maxillary sinus mucosa.